2015
DOI: 10.3390/su7056212
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Decomposed Theory of Planned Behaviour to Predict the Usage Intention of the Electric Car: A Multi-Group Comparison

Abstract: An Extended Decomposed Theory of Planned Behaviour (DTPB) is developed that integrates emotions towards car driving and electric cars as well as car driving habits of the DTPB, and is empirically validated in a Belgian sample (n = 1023). Multi-group comparisons explore how the determinants of usage intention are different between groups of consumers differing in environmentally-friendly behaviour, environmental concern, innovativeness and personal values. Besides attitudes, media, perceived complexity, compati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
85
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 111 publications
(189 reference statements)
13
85
0
3
Order By: Relevance
“…First, corroborating prior studies on electric car adoption, our results confirm that both attitude [9,47] and subjective norm [49][50][51] have an impact on EV buying intention. Specifically, the more positive is the attitude, the higher is the behavioral intention, and the greater is the perceived social pressure, the higher is the intention to purchase the car.…”
Section: Discussion Managerial Implications and Hints For Future Ressupporting
confidence: 79%
See 1 more Smart Citation
“…First, corroborating prior studies on electric car adoption, our results confirm that both attitude [9,47] and subjective norm [49][50][51] have an impact on EV buying intention. Specifically, the more positive is the attitude, the higher is the behavioral intention, and the greater is the perceived social pressure, the higher is the intention to purchase the car.…”
Section: Discussion Managerial Implications and Hints For Future Ressupporting
confidence: 79%
“…In the field of alternative fuel car purchase intention, ATT has been found positively related to both hybrid-electric [9] and full electric vehicles [47]. Accordingly, our hypothesis is the following:…”
Section: The Theory Of Reasoned Actionmentioning
confidence: 68%
“…The more positive the individual attitude, the more support from relevant persons as well as the more perceived autonomic control, the higher behavioral intention of the person [33]. To date, TPB has been applied to predict consumers' intention and behavior in a wide range of areas, including environmentally sustainable products [36], electric vehicles [37], green hotels [38,39], and energy conservations [40,41]. This theory is a powerful model in explaining environmentally friendly behavior [42].…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…Strongly innovative individuals may take personality considerations into account in a different way than less innovative consumers. Previous research has shown that, in this early stage of the adoption of electric cars, these factors do not play an important role in the adoption intention process [76]. Nevertheless, as the adoption process progresses, these factors may play an increasingly important role.…”
Section: Future Researchmentioning
confidence: 97%